Chromoblastomycosis mimicking Squamous Cell Carcinoma: a case report - BMM Kayastha; R Shrestha; Pan Shrestha; A Karki (Nepal Journal of Dermatology, Venereology & Leprology)
Chromoblastomycosis (CM), a chronic subcutaneous mycosis, is caused by several dematiaceous fungi, the most common being Fonsecaea pedrosoi . It usually occurs in the lower extremities following traumatic implantation of the organisms. We are reporting a case of rapidly developing case of CM on the unilateral lower limb with a fungating mass like ulcerative lesion and hyperkeratotic warty growth. We could not explain the pattern of this rapid growth which seems to be one of the rare presentations. Scraping from a verrucous lesion in potassium hydroxide preparation revealed mycelia arising from sclerotic bodies The histopathology from the warty lesion showed granulomatous lesion without muriform or medlar bodies. The histopathology from the ulcerative lesion did not show any malignant changes. Our case responded very well to itraconazole. This case is presented here for the rapidity of growth and the development of a fungating mass and bleeding that simulated the behaviour of squamous cell carcinoma.